Opportunistic cooperative spectrum sensing based on eigenvalue ratio of random matrix - Wuji ZHANG; Shunlan LIU; Jianrong BAO (Dianxin kexue)
To overcome the deficiencies of low detection probability of traditional spectrum sensing,an EROC spectrum sensing algorithm based on the eigenvalue ratio of a random matrix was proposed.Based on the random detection theory,it used double thresholds and opportunistic cooperation to improve of traditional maximum and minimum eigenvalue (MME) algorithm,and it retained the advantages of the traditional energy detection algorithm.Moreover,on the premise of known false alarm probability,the decision threshold was deduced,and the odd-even slot division was used to effectively realize opportunistic cooperation in reception.Simulation results show that the proposed spectrum sensing algorithm has higher detection probability than MME algorithms in case of low signal-to-noise ratio and low false alarm probability.Therefore,it is suitable for application in wireless communications with deteriorate transmission channels.